MANAJEMEN PEMBELAJARAN PAI BERBASIS DIFERENSIASI UNTUK MENUMBUHKAN SIKAP MODERASI BERAGAMA SISWA DI SMPN 2 GARUT - Elisa Harisah; Yufi Mohammad Nasrullah; Fiqra Muhamad Nazib (Jurnal Manajemen Pendidikan, 2026)
Objective: this study aims to analyze the management of differentiated Islamic Religious Education (PAI) learning in fostering students’ religious moderation attitudes at SMPN 2 Garut, focusing on planning, organizing, implementation, and evaluation processes. Methods: This research employed a qualitative approach with a descriptive method. Data were collected through interviews, observations, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques. Results: The findings reveal that learning planning was conducted by considering students’ differences in abilities, interests, and learning styles through flexible grouping, block scheduling, and a supportive learning environment. The implementation of learning combined classical, group, and individual approaches, supported by varied methods and media. Meanwhile, evaluation was conducted comprehensively using authentic assessment techniques, including observation, self-assessment, and peer assessment, covering cognitive, affective, and psychomotor aspects. Novelty: This study offers a comprehensive perspective by integrating learning management functions with differentiated learning approaches in PAI to strengthen students’ religious moderation, which is still limited in previous studies.